Initial Reports of the Deep Sea Drilling Project 1986
DOI: 10.2973/dsdp.proc.87.118.1986
|View full text |Cite
|
Sign up to set email alerts
|

Petrography and Geochemistry of Volcanic Ash Layers from Leg 87A, Nankai Trough (South Japan)

Abstract: In the Leg 87A holes, 45 ash layers were sampled in Recent to upper Pliocene strata. The main volcanogenic deposits came from single eruptions or subcontemporaneous eruptions of cognate volcanoes. Some of them are mixed ashes produced from multiple eruptions and accumulated in reworked sediments. The petrographic and geochemical patterns indicate rhyolitic and dacitic compositions; andesitic glasses are scarce. We infer a magmatic affinity with calc-alkaline sources and a possible origin from the volcanic arc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
(9 reference statements)
4
11
0
Order By: Relevance
“…The geochemistry of the ashes is consistent with known explosive andesitic to rhyolitic volcanism in the Japanese Honshu and Izu-Bonin arcs (Pouclet et al, 1986;Masuda et al, this volume). The geochemistry of the circa-14-Ma rhyolitic pyroclastics at the base of Site 808 is different than for the overlying, younger ashes and tuffs, which suggests a different provenance.…”
Section: General Sedimentological Trends At Site 808supporting
confidence: 74%
“…The geochemistry of the ashes is consistent with known explosive andesitic to rhyolitic volcanism in the Japanese Honshu and Izu-Bonin arcs (Pouclet et al, 1986;Masuda et al, this volume). The geochemistry of the circa-14-Ma rhyolitic pyroclastics at the base of Site 808 is different than for the overlying, younger ashes and tuffs, which suggests a different provenance.…”
Section: General Sedimentological Trends At Site 808supporting
confidence: 74%
“…The chemical heterogeneity of the pyroclastic material is consistent with the documented range of andesitic to rhyolitic sources of explosive volcanism on the Japanese Islands. We agree with the assessment of Pouclet et al (1986) who identified the active volcanic arc of southwest Japan, including the Izu-Honshu collision zone, as the principal source of Quaternary ash ( Figure 1). Other possible sources would be the explosive volcanic centers on Kyushu and the Izu-Bonin arc.…”
Section: Pyroclastic Contributions To Shikoku Basinsupporting
confidence: 68%
“…We agree with the assessment of Pouclet et al (1986), who identified the principal pyroclastic source as the Quaternary volcanic arc of southwest Japan, including the Izu-Honshu collision zone (Fig. 1).…”
Section: Volcanic Ash Geochemistrysupporting
confidence: 66%
“…Chemical data are sparse for Site 297, so it is not clear how much of the disparity is due to ash alteration with depth, as opposed to chemical differences in the volcanic sources that supplied Sites 297 and 808, respectively. Chemical analyses of volcanic glass from Sites 582 and 583 (Pouclet et al, 1986) add to the complexity. These ash layers also yield consistently higher silica contents than the background mudstones (Fig.…”
Section: Volcanic Ash Geochemistrymentioning
confidence: 99%